Application of the thixotropic elasto-viscoplastic model as a structure probing technique for acid milk gel suspensions. (April 2018) - Javanmard, Marjan; Wong, Edeline; Howes, Tony; Stokes, Jason R.
Abstract: The rheology of acid milk gels is investigated as an elasto-viscoplastic thixotropic fluid. The gel is a colloidal protein network that upon shear is transformed into suspension of aggregates where the original rheology of the gel is not recoverable. It is shown that the measured characteristic size of the aggregates is directly proportional to a structural parameter (λ) obtained from rheological measurements. This supports the use of the λ in elasto-viscoplastic constitutive models as a representation of the changing structure in the suspension. λ also correlates to the aggregate particle size after initially breaking down the structure at high shear rate and then allowing the structure to recover at lower shear rates. Following this shear breakdown/recovery, a broader particle size distribution is observed compared with the results obtained during breakdown of the initial set gel. This structural difference may be critically linked to the thixotropic rheological properties of the sheared gels. The outcomes from this research pave the way for mechanistically predicting and quantifying shear processing-structure-property relationships for acid milk gels and other related dairy foods. Highlights: Elastic-viscoplastic models have application in engineering soft materials and foods. Characteristic particle size within sheared acid milk gels is reflected by its rheology. Rheological structural parameter provides in situ quantification of shear process-structure-property relationships.